2012
DOI: 10.1136/annrheumdis-2011-200837
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum levels and tissue expression of matrix metalloproteinase-12 in patients with systemic sclerosis: correlation with severity of skin and pulmonary fibrosis and vascular damage

Abstract: MMP-12 levels are increased in patients with SSc and are associated with severity of skin and pulmonary fibrosis and peripheral vascular damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 33 publications
3
73
0
4
Order By: Relevance
“…In isolated endothelial cells from the lungs of BLM-injected mice, we observed a marked up-regulation in MMP12, which was significant at 4 weeks (Figure 2A). These data suggest that endothelial cells are damaged in this model of chronic lung injury, similar to the endothelial damage associated with SSc (22,23).…”
Section: Endothelial Cells Are Damaged In Response To the Subcutaneousupporting
confidence: 58%
See 3 more Smart Citations
“…In isolated endothelial cells from the lungs of BLM-injected mice, we observed a marked up-regulation in MMP12, which was significant at 4 weeks (Figure 2A). These data suggest that endothelial cells are damaged in this model of chronic lung injury, similar to the endothelial damage associated with SSc (22,23).…”
Section: Endothelial Cells Are Damaged In Response To the Subcutaneousupporting
confidence: 58%
“…We observed an increase of vWF expression in endothelial cells, suggesting injury to the endothelium. In a recent report by Manetti and colleagues (23), increased MMP12 in the serum of patients with scleroderma correlated with the severity of pulmonary fibrosis and vascular injury. Consistent with this, we found that MMP12 was up-regulated in endothelial cells from mice treated with BLM.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Biomarkers of endothelial dysfunction and impaired angiogenesis have been also suggested in SSc. These include ADAMTS-13 enzyme, endothelin-1, endothelial growth factor receptor-1 and -7, and matrix metalloproteinase-12 [3,4].…”
Section: Introductionmentioning
confidence: 99%